Earnings Quality Pasca Penerapan PSAK Konvergensi IFRS - Zaitul; Melani Sri Wahyuni; Dandes Rifa; Desi Ilona (Universitas Serang Raya, 2023)
This study aims to determine the effect of IFRS adoption on earnings quality with corporate governance variables as moderating. Sampling uses non probability with purposive sampling technique. 245 companies-years are used as samples. The data used is secondary. Data collection methods are obtained from annuals report on the website of Indonesia stock exchange (IDX), company websites and other electronic sources. Hypotheses are tested using moderate regression analysis (MRA). The results showed that i) IFRS adoption had no effect on earnings quality; 2) institutional ownership, managerial ownership and the board of commissioners do not affect earnings quality; 3) institutional ownership, managerial ownership and the board of independent commissioners cannot moderate the relationship of IFRS adoption and earnings quality.